PROTECTION AGAINST NUISANCES RELATED TO A CONSTRUCTION OF A BUILDING – SELECTED ISSUES - Anna Wilk (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper deals with protection against nuisances related to a construction of a building. The nuisances frequently take place and in connection with the increase of the density of buildings it is possible that they will become more burdensome. Protection against such nuisances may be realized at two levels: civil law and administrative. Civil law protection measures cover primarily a negatory claim1 and a claim for withholding the construction2 . Administrative law protection is possible under the provisions of the act on construction law, which enable the people living in the neighbourhood of the planned investment to participate in the proceedings concerning the construction permit and thereby provide proactive protection of their interest. Application of both civil law and administrative protection measures against nuisances related to a construction of a building is connected with difficulties: a misinterpretation of provisions, their unclear structure and a lack of legal regulation of certain essential issues like the administrative decision status in the civil proceeding. In the paper the focus is on the most important of the mentioned problems and presents the solutions.